A metastatic ureteral tumor successfully treated with multidisciplinary therapy including radiotherapy. Issue 3 (3rd March 2023) - Kawaguchi, Yoshihiro; Naritomi, Kazuya; Kawagoe, Nobutoshi; Matsunaga, Yoshihiro; Ogasawara, Naoyuki; Igawa, Tsukasa
Abstract : Introduction: Metastatic ureteral tumors are difficult to diagnose pathologically. Treatment is only available for the primary disease, and prognosis is generally poor. Case presentation: A 63‐year‐old patient with a history of gastric cancer presented with asymptomatic right‐sided hydronephrosis. Ureteroscopic examination revealed tissue in the ureter consistent with gastric cancer. The lesion was localized, and the patient was treated with chemotherapy and radiotherapy as part of a multidisciplinary treatment. The prognosis was better than in other reports. To the best of our knowledge, this is the first case of a patient with metastatic gastric cancer who received multidisciplinary treatment including radiotherapy and had a good prognosis. Conclusion: In cases where a localized metastatic ureteral tumor cannot be ruled out, ureteroscopy is an effective therapeutic strategy.